Croatian Dual - Kraljević, Marija prevoditeljica (2008)
This paper aims at investigating the category of dual (more precisely, paucal) in Croatian. This is a rather controversial issue for Croatian linguists, who have mostly avoided mentioning this category in the accounts of present– day standard Croatian. This has been done presumably in order to avoid accounting for an asymmetric morphological system, since dual is not present in verb paradigms. In Croatian grammars, dual forms (forms of nouns following numerals dva, tri, ~etiri (two, three, four) are interpreted as either genitive singular (for masculine and neuter gender: dva dje~aka, tri pitanja – two boys, three questions) or nominative plural (for feminine gender: dvije knjige – two books). This account is somewhat unusual because it proposes that masculine and neuter nouns on one hand, and feminine nouns on the other, have completely different morphosyntactic features within the same type of phrase (quantifier + noun). Even though the noun forms dje~aka i pitanja are homonymous to the respective genitive singular forms, and the form knjige to nominative plural forms, we can prove that these forms are not the same by inserting an adjective as a premodifier (which agrees with the noun in gender, number and case). The genitive singular form of the phrase hrabri dje~ak (the brave boy) is hrabroga dje~aka, and the form of this phrase in combination with the quantifier dva (two) is dva hrabra dje~aka, which proves these two to be distinct forms, as well as indicate that the phrase (dva) hrabra dje~aka belongs to a separate number paradigm, since it doesn’ t fit into any of the forms of the singular and plural nominal paradigms. The existing analyses of dual forms are not problematic only within the morphological system, but have repercussions for the syntactic analysis as well. However, what is even more important for this research, disregarding the existence of the dual paradigm, and the inadequate interpretations of its forms, prevent us from gaining insight on semantic and conceptual basis of this grammatical category. Cognitive Grammar provides a framework for this analysis, in terms of the semantic difference in the profiled mass of dual forms on one hand and plural forms on the other. This research will offer an analysis of dual forms within Croatian morphological system, present arguments for the inclusion of the disregarded dual paradigm into the account of Croatian grammar, as well as try to offer a cognitively based interpretation of this category, in relation to the category of plural.